2020
DOI: 10.1021/acssuschemeng.0c03424
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Impact of Thermal Binder Removal for Direct Li-Ion Battery Recycling

Abstract: Li-ion battery recycling will become critical to the management of end-of-life batteries from electric vehicles. Currently, it is a challenge to create a profitable recycling process, which is made more difficult by the reduction in cathode cobalt content. Maintenance of the cathode structure throughout the recycling process can yield increased revenues that may make recycling profitable. This method will require careful removal of the PVDF binder and carbon black, which can be achieved through thermal process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…[ 139–141 ] Obsolete binders and additives will have to be removed in advance to further recovery steps of active materials. [ 142,143 ] Despite recent progress regarding direct recovery of electrode active materials, [ 144,145 ] an additional upscaling of electrode chemistries will be necessary in many cases, as decommissioned batteries will likely contain outdated electrode chemistries. Although first results have been published, for example, the upscaling of LCO to LiNi 1/3 Mn 1/3 Co 1/3 O 2 , [ 146 ] this represents one of the major challenges to be tackled within the next few years. Several recycling processes are likely to cause impurities in directly recovered electrodes such as aluminum or copper fragments from the current collectors.…”
Section: Battery 2030+: Research Areasmentioning
confidence: 99%
“…[ 139–141 ] Obsolete binders and additives will have to be removed in advance to further recovery steps of active materials. [ 142,143 ] Despite recent progress regarding direct recovery of electrode active materials, [ 144,145 ] an additional upscaling of electrode chemistries will be necessary in many cases, as decommissioned batteries will likely contain outdated electrode chemistries. Although first results have been published, for example, the upscaling of LCO to LiNi 1/3 Mn 1/3 Co 1/3 O 2 , [ 146 ] this represents one of the major challenges to be tackled within the next few years. Several recycling processes are likely to cause impurities in directly recovered electrodes such as aluminum or copper fragments from the current collectors.…”
Section: Battery 2030+: Research Areasmentioning
confidence: 99%
“…4 section I, the evolved gases (C x H y , CO 2 , and H 2 O) indicate dissociation or decomposition of an organic compound, which could be the binder and/or residual solvents. PVDF, as a binder, is spread on the particles to maintain a bond between the cathode/anode active material, current collectors, and acetylene black [29,30]. With the decomposition of PVDF, it is possible for the acetylene black to oxidize.…”
Section: Bm From Lco Batteriesmentioning
confidence: 99%
“…The nano-particles of carbon black were not detectable with this analytical tool which has a micrometer-scale resolution. However, Ross et al (2020) reported that carbon black decomposes at around 500°C, and therefore it should not be present after the pyrolysis stage. If residuals of carbon black remain, they will not have a significant impact on the general carbon content.…”
Section: Figure 9 Example Of the Lithium Metal Oxides Caractegorizer With Lco And Nmc Categories Applied To The Different Size Fractions mentioning
confidence: 99%